2022
DOI: 10.2118/209607-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Interwell Connectivity in Waterflooding Reservoirs with Graph-Based Cooperation-Mission Neural Networks

Abstract: Summary Interwell connectivity plays a key role in waterflooding for guiding water injection. The existing works focus on the response relationship between one injection well and one production well. No research has explored the structural information of waterflooding on a well pattern. To address this challenge, this paper proposes cooperation-mission neural networks for interwell connectivity with graph information. Specifically, we propose some assumptions based on the petroleum domain to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…According to Hamdy et al (2019), water flooding evaluation in a certain field is essential to be utilized as a valuation basis to measure water flooding success. The intended evaluation is a connectivity analysis of injection and production wells (Zeng et al, 2022). This connectivity analysis is also enhanced by a number of analyses such as Hall Plot analysis to acknowledge problems occurring in the injection well, Chan's WOR analysis to identify problems in the production well, and Voidage Replacement Ratio (VR) analysis to compare injection and production volumes.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hamdy et al (2019), water flooding evaluation in a certain field is essential to be utilized as a valuation basis to measure water flooding success. The intended evaluation is a connectivity analysis of injection and production wells (Zeng et al, 2022). This connectivity analysis is also enhanced by a number of analyses such as Hall Plot analysis to acknowledge problems occurring in the injection well, Chan's WOR analysis to identify problems in the production well, and Voidage Replacement Ratio (VR) analysis to compare injection and production volumes.…”
Section: Resultsmentioning
confidence: 99%
“…Its value has a significant impact on water invasion and rock porosity expansion. Previous studies have suggested that under high-pressure conditions in reservoirs, the reservoir water compressibility factor remains relatively constant with pressure changes, but the pore compressibility factor exhibits noticeable variations [21,22]. Currently, there are three main methods for determining the pore compressibility factor: the empirical formula method, experimental measurement method, and theoretical calculation method.…”
Section: Introductionmentioning
confidence: 99%